The patrimonial responsibility of the Public Administration in extracurricular and complementary activities: on the jurisprudence of the Supreme Court - Delgado Moral, Carmen (Avances en Supervisión Educativa, 2018)
The study examines the patrimonial responsibility of the Public Administration in non-higher education teaching centers during the development of extracurricular and complementary activities. After the amendment of the Civil Code of 1991, there is a transfer of responsibility from the teacher to the holders of non-university teaching centers for crimes or misdemeanors incurred by students under the age of eighteen during the periods in which they are under the control or supervision of the faculty in the center (during school activities, extracurricular or complementary activities); therefore, the articulation of that responsibility of the owners of the centers for the culpable or negligent actions from their agents will be studied. To do this, we review the responsibility of the teacher through the study of significant sentences, from which it is concluded that the motivating principle of this responsibility is the guilt. We will study the imputability of the damage to the Public Administration based on a normal or unusual operation of the service and we will analyze, after the study of certain Supreme Court decisions, cases in which it is considered that the diligence of a householder has not been used for the prevention of the damage (physical or psychic).
Keywords: education; school center; extra-school activities; complementary activities; patrimonial responsibility; public administration; hurt; guilt; rights